Weapons of opportunity : a novel - Brown, Dale, 1956- (Brown, Dale, 1956- Nick Flynn novel, 2023)
"When Nick Flynn left the US Air Force to join the Quartet Directorate, he did so with the full knowledge that no one could ever know. This covert private force--called Four by its members--promised him the chance to lead his own missions and make his own decisions. When a former senior CIA executive goes dark, Flynn and his team are ready to step in. What begins as a quiet check on his home turns into a firefight against a familiar enemy who is more dangerous than ever"--